Cardiovascular risk factor changes in Finland, 1972-1997 - Vartiainen, Erkki; Jousilahti, Pekka; Alfthan, Georg; Sundvall, Jouko; Pietinen, Pirjo; Puska, Pekka (International Journal of Epidemiology, 2000)
Background The cardiovascular risk factor levels of the population have been assessed in Finland since 1972. In the beginning the surveys were done to evaluate the North Karelia Project, which was a community-based preventive programme. A national cardiovascular disease (CVD) prevention strategy was developed and implemented during the late 1970s. Subsequently, a national cardiovascular risk factors monitoring system was developed to assess the effectiveness of the national strategy. Methods Cross-sectional population samples were studied in 1972 and 1977 in North Karelia and Kuopio provinces in eastern Finland. An area in southwestern Finland was included in 1982, followed by the Helsinki metropolitan area in 1992 and Oulu province in northern Finland in 1997. A total of 19 761 men and 20 761 women aged 30–59 participated in the six surveys (1972, 1977, 1982, 1987, 1992, 1997). Results The serum cholesterol levels of both genders have continuously declined. Systolic blood pressure levels have declined since 1972, but no further decline in diastolic blood pressure was found in 1997. Smoking prevalence among men continued to decline mainly due to an increase in the percentage of never-smokers. For the first time the increase in smoking prevalence among women levelled off and started to decline, mainly because the number of female quitters had increased. Conclusions These data suggest that the cardiovascular health programme in Finland has succeeded in decreasing the general risk factor level of the population.